2011
DOI: 10.1016/j.clinimag.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional bold MRI: advantages of the 3 T vs. the 1.5 T

Abstract: We quantitatively evaluate the benefits of a higher field strength for functional brain MRI (fMRI) based on the blood oxygenation level-dependent contrast. The 3-T fMRI shows a higher sensitivity for the motor and somatosensory stimulation and more specific localization in the grey substance. The 3-T fMRI detects additional areas of activation with the motor paradigm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…All approaches effectively increased the BOLD sensitivity in the individual, but the increased functional sensitivity at the single subject level only partly translated into an increased statistical power in group analyses. For example, increasing the field strength from 1.5 T to 3 T improved the functional sensitivity by only up to 30% in group analyses as quantified by t-value increases ( Kruger et al, 2001 , Krasnow et al, 2003 , Garcia-Eulate et al, 2011 ), which is much less than the improvements of ~ 100% observed in single subject analyses (e.g., 1.5 T vs. 4 T in ( Gati et al, 1997 )). Although increasing the number of RF receive coils and channels from 12 to 32 increased the sensitivity in single subject analyses by about 25% ( Kaza et al, 2011 ), again only small and equivocal differences were found in group analyses ( Kaza et al, 2011 ).…”
Section: Introductionmentioning
confidence: 79%
“…All approaches effectively increased the BOLD sensitivity in the individual, but the increased functional sensitivity at the single subject level only partly translated into an increased statistical power in group analyses. For example, increasing the field strength from 1.5 T to 3 T improved the functional sensitivity by only up to 30% in group analyses as quantified by t-value increases ( Kruger et al, 2001 , Krasnow et al, 2003 , Garcia-Eulate et al, 2011 ), which is much less than the improvements of ~ 100% observed in single subject analyses (e.g., 1.5 T vs. 4 T in ( Gati et al, 1997 )). Although increasing the number of RF receive coils and channels from 12 to 32 increased the sensitivity in single subject analyses by about 25% ( Kaza et al, 2011 ), again only small and equivocal differences were found in group analyses ( Kaza et al, 2011 ).…”
Section: Introductionmentioning
confidence: 79%
“…Although fMRI studies had not addressed such a comparison in clinical contexts, a number of methodological reports showed higher BOLD sensitivity at a field of 3T as compared to 1.5T in areas such as sensoriomotor cortices (e.g. SMA) [21] , [22] or the parahippocampal cortex [23] , both known to be engaged in the mental imagery tasks here studied. While our group results seem to be in agreement with the above studies, it is important to note that the differences were limited to small clusters in a minority of the regions studied.…”
Section: Discussionmentioning
confidence: 96%
“…OXYGEN-SENSITIVE magnetic resonance imaging (MRI) has been increasingly used in clinical research to investigate neuronal activation, kidney function, and tumor hypoxia (1)(2)(3)(4)(5)(6)(7). Two different mechanisms involved in oxygen-induced MR effects are: 1) T 1 relaxation time changes affected by paramagnetic T 1 -shortening properties of molecular O 2 in tissues (5,8,9), and 2) susceptibility-related T Ã 2 increase created by decreased concentration of intravascular deoxyhemoglobin upon breathing O 2 (1,4,9,10).…”
mentioning
confidence: 99%